FRI0150 Depression, Inflammation and Mortality in Patients with Rheumatoid Arthritis. (15th July 2016) - Kleinert, S.; Marx, A.; Faller, H.; Tony, H.-P.; Feuchtenberger, M.; Kneitz, C.; Lehmann, S.; Angermann, C.; Ertl, G.; Störk, S.; Breunig, M.
Abstract : Background: Patients with rheumatoid arthritis (RA) have a high prevalence of depressive symptoms and an increased mortality. Objectives: The current prospective follow-up study investigates prevalence of depression, its association with inflammation and mortality in RA patients. Methods: 764 consecutive patients attending the rheumatology outpatient department of the University Hospital Würzburg underwent a comprehensive cardiovascular (CV) risk assessment. Inflammation in RA patients was characterized by DAS28 and CRP. Quality of life and depressive symptoms were investigated by SF-36 and PHQ-9 (range 0–27 score points), respectively. A PHQ score ≥15 points is considered indicative for severe depressive symptoms. Results: 352 subjects suffered from rheumatoid arthritis (RA: 79.5% female, 64.9% RF positive, mean age 54.3 (SD 14.3)), Severe or moderate depressive symptoms were prevalent in 6.6%, respectively 14.4% of RA patients. DAS28, but not CRP, was significantly associated with the prevalence of depressive symptoms (r=0.26 (p<0.001), figure A, table 1 ). Patients with severe depressive symptoms (PHQ 9 ≥15) had an increased a HR of 6.42 (95% CI, 2.04 – 20.2, p=0.004) for mortality compared to patients with a PHQ ≤14 (figure B ). Conclusions: DAS28 in RA patients was associated with severity of depressive symptoms. Severely depressed patients had an increased mortality. Disclosure of Interest: None declared